A two-photon fluorescent probe for specific detection of hydrogen sulfide based on a familiar ESIPT fluorophore bearing AIE characteristics12. Issue 35 (13th April 2017) - Chen, Liyan; Wu, Di; Lim, Chang Su; Kim, Dayoung; Nam, Sang-Jip; Lee, Woolin; Kim, Gyungmi; Kim, Hwan Myung; Yoon, Juyoung
Abstract : A two-photon fluorescent probe based on an ESIPT fluorophore bearing AIE characteristics was utilized to detect H2 S. Abstract : Hydrogen sulfide (H2 S) is a signaling gasotransmitter, which plays various roles in modulating the functions of different systems. In this study, a "turn-on" fluorescent probe for H2 S was developed. The probe, whose design is based on a familiar excited state intramolecular proton transfer (ESIPT) fluorophore bearing aggregation-induced emission (AIE) characteristics, was found to exhibit an 80-fold fluorescence enhancement along with a large Stokes shift upon the addition of H2 S. Furthermore, the probe was successfully utilized to detect H2 S in HeLa cells with both one-photon and two-photon microscopy.